Metode Latihan Kombinasi Papan Luncur dan Bagian-Keseluruhan untuk Meningkatkan Kemampuan Renang Gaya Bebas Siswa Sekolah Dasar - Dinda Aulia Paramitha; Januar Abdilah Santoso (Jurnal Porkes, 2026)
The swimming extracurricular program in Samarinda faces challenges in achieving meaningful skill improvement due to infrequent practice sessions (only once a week) and suboptimal traditional teaching methods. This study aims to test the effectiveness of integrating kickboard exercises with the part-and-whole method on improving freestyle swimming performance among elementary school students. The research method employed a one-group pretest-posttest pre-experimental design. The participants consisted of 20 students aged 10–12 years from SD Terpadu Muhammadiyah 4 Samarinda. The intervention was conducted over 12 weeks (April-June 2025) with a frequency of one 90-minute session per week. The instruments used were a 20-meter freestyle swimming test and a technical skills checklist. Data analysis utilized a paired-sample t-test and effect size calculations with SPSS version 26. Results There was a significant improvement in swimming time (pretest: 24.85 ± 5.73 seconds; posttest: 15.42 ± 2.36 seconds; p < 0.001) and technical skill scores (pretest: 11.25 ± 2.48; posttest: 19.35 ± 2.21; p < 0.001). Cohen’s d effect size of 2.16 indicates a large practical significance. Conclusion Integrating the kickboard with the part-and-whole method effectively improves freestyle swimming performance in elementary school students with a weekly training frequency. Further research is recommended using a randomized controlled trial with a control group and measuring long-term skill retention.